Testosterone and dihydrotestosterone modulate the redox homeostasis of endothelium. (30th January 2022) - Koukoulis, George N.; Filiponi, Maria; Gougoura, Sofia; Befani, Christina; Liakos, Panagiotis; Bargiota, Αlexandra
Abstract: The predominance of cardiovascular diseases among men compared to premenopausal women has been attributed to testosterone, which is implicated in vascular remodeling. Molecular mechanisms underlying its role have not been clarified but oxidative stress‐induced inflammation may be important. We therefore investigated in vitro the effects of testosterone and dihydrotestosterone, (a nonaromatized androgen), on redox homeostasis in absence (basal conditions) and after corticotropin‐releasing hormone‐induced pro‐oxidant action in macroendothelial cells. More specifically, we explored their role on well‐established antioxidant enzymes activity, namely endothelial nitric oxide synthase, superoxide dismutase, catalase, and glutathione. We observed that both androgens significantly increased the intracellular reactive oxygen species levels, endothelial nitric oxide synthase activity, nitric oxide concentration as well as superoxide dismutase activity and decreased catalase activity. These effects of Testosterone and DHT were reversed in the presence of the androgen receptor antagonist, flutamide. Moreover, testosterone and dihydrotestosterone similarly enhanced the stimulatory effect of corticotropin‐releasing hormone on intracellular reactive oxygen species levels and superoxide dismutase activity but did not influence the inhibitory effect on endothelial nitric oxide synthase activity, nitric oxide release and catalase activity. Finally, androgens did not have a detectable effect on glutathione levels or the glutathione/glutathione plus glutathione disulfide ratio. Our results reveal that testosterone and DHT rise the intracellular redox threshold of the endothelial cell and increases NO synthesis. These findings suggest that the action of testosterone is affected by the redox status of the endothelium and help to explain its controversial effects on the cardiovascular system.